2013
DOI: 10.1161/circgenetics.113.000138
|View full text |Cite
|
Sign up to set email alerts
|

Exome Sequencing and Systems Biology Converge to Identify Novel Mutations in the L-Type Calcium Channel, CACNA1C , Linked to Autosomal Dominant Long QT Syndrome

Abstract: Background Long QT syndrome (LQTS) is the most common cardiac channelopathy with 15 elucidated LQTS-susceptibility genes. Approximately 20% of LQTS cases remain genetically elusive. Methods and Results We combined whole exome sequencing (WES) and bioinformatic/systems biology to identify the pathogenic substrate responsible for non-syndromic, genotype-negative, autosomal dominant LQTS in a multigenerational pedigree and established the spectrum and prevalence of variants in the elucidated gene among a cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
104
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(108 citation statements)
references
References 45 publications
1
104
2
1
Order By: Relevance
“…23 the ltCC is important for excitation-contraction coupling in the heart and mediates an inward depolarizing current in cardiomyocytes. functional characterization of the mutation using a whole-cell patch-clamp technique in hek293 cells revealed a gain-of-function with increased iCa,l and increased cell surface expression of the mutant ion channel compared to wild type.…”
Section: Cacna1c-lqtsmentioning
confidence: 99%
See 1 more Smart Citation
“…23 the ltCC is important for excitation-contraction coupling in the heart and mediates an inward depolarizing current in cardiomyocytes. functional characterization of the mutation using a whole-cell patch-clamp technique in hek293 cells revealed a gain-of-function with increased iCa,l and increased cell surface expression of the mutant ion channel compared to wild type.…”
Section: Cacna1c-lqtsmentioning
confidence: 99%
“…importantly, although CaCna1C perturbations had been implicated previously in timothy syndrome (ts) and incorrectly given the genotype place holder as lQt8, this was the first demonstration that CaCna1C was a bona fide lQts-susceptibility gene, extending the breadth of distinct CaCna1C-related arrhythmogenic phenotypes. subsequently, mutational analysis of 103 unrelated lQts genotype-negative/phenotype-positive patients identified three additional CaCna1C missense mutations, suggesting that CaCna1C mutations may explain as much as 4% to 5% of genetically elusive lQts 23 or approximately 1% of lQts altogether. interestingly, three of the four mutations (k834d, p857l, and p857r) localized to the same critical pest-domain in the ii-iii linker of the ltCC, an amino acid sequence motif that represents an important signal for rapid protein degradation and ltCC channel stability.…”
Section: Cacna1c-lqtsmentioning
confidence: 99%
“…This mutation in Ca V 1.2 also revealed a complex channel phenotypes, including loss of current density and inactivation in combination with increased window and late currents [83]. By whole-exome sequencing and bioinformatics/systemic biology, Boczek et al further identified 4 novel mutations of CACNA1C in LQTS, including p.K834E, p.P857R, p.P857L, and p.R1906Q [84], 3 of which were located at the conserved proline, glutamic acid, serine and threonine rich (PEST) domain of Ca V α 1 II-III loop, this domain acts to proteolytic signaling through the cellular quality control system [85]. Functionally, p.P857R mutation, cosegregated with the disease within the pedigree, significantly increased calcium currents and surface membrane expression of the channel as compared with wild type (WT) Ca V 1.2 channel [84].…”
Section: Long Qt and Timothy Syndromesmentioning
confidence: 99%
“…By whole-exome sequencing and bioinformatics/systemic biology, Boczek et al further identified 4 novel mutations of CACNA1C in LQTS, including p.K834E, p.P857R, p.P857L, and p.R1906Q [84], 3 of which were located at the conserved proline, glutamic acid, serine and threonine rich (PEST) domain of Ca V α 1 II-III loop, this domain acts to proteolytic signaling through the cellular quality control system [85]. Functionally, p.P857R mutation, cosegregated with the disease within the pedigree, significantly increased calcium currents and surface membrane expression of the channel as compared with wild type (WT) Ca V 1.2 channel [84]. Interestingly, p.R1906Q locates one amino acid away from α 1C C-terminal STIM1 (stromal-interacting molecule 1, a calcium store sensor) binding domain, which may affect STIM1-mediated Ca V 1.2 channel gating inhibition and channel internalization [86,87].…”
Section: Long Qt and Timothy Syndromesmentioning
confidence: 99%
See 1 more Smart Citation